1997
DOI: 10.1086/304483
|View full text |Cite
|
Sign up to set email alerts
|

The Cooling of CO White Dwarfs: Influence of the Internal Chemical Distribution

Abstract: White dwarfs are the remnants of stars of low and intermediate masses on the main sequence. Since they have exhausted all of their nuclear fuel, their evolution is just a gravothermal process. The release of energy only depends on the detailed internal structure and chemical composition and on the properties of the envelope equation of state and opacity ; its consequences on the cooling curve (i.e., the luminosity vs. time relationship) depend on the luminosity at which this energy is released.The internal che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
335
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(357 citation statements)
references
References 31 publications
(46 reference statements)
15
335
3
4
Order By: Relevance
“…Maybe the most severe shortcoming of these models is the (unrealistic) ramp-like shape of the core carbon-oxygen chemical profiles. These DA models were the basis of the very important asteroseismological studies on the DAVs G 29−38 (Bradley & Kleinman 1997), G 117−B15A and R 548 (Bradley 1998 , and the core chemical structure extracted from the evolutionary calculations of Salaris et al (1997). The employment of very smooth chemical interfaces, as shaped by chemical diffusion, revealed that the use of the trace element approximation is inappropriate in pulsational studies.…”
Section: Da White Dwarf Models and Asteroseismological Studies Of Davsmentioning
confidence: 99%
“…Maybe the most severe shortcoming of these models is the (unrealistic) ramp-like shape of the core carbon-oxygen chemical profiles. These DA models were the basis of the very important asteroseismological studies on the DAVs G 29−38 (Bradley & Kleinman 1997), G 117−B15A and R 548 (Bradley 1998 , and the core chemical structure extracted from the evolutionary calculations of Salaris et al (1997). The employment of very smooth chemical interfaces, as shaped by chemical diffusion, revealed that the use of the trace element approximation is inappropriate in pulsational studies.…”
Section: Da White Dwarf Models and Asteroseismological Studies Of Davsmentioning
confidence: 99%
“…These improved cooling sequences are based on the Salaris et al (1997) but including an accurate treatment of the crystallization process of the carbon-oxygen core, considering phase separation upon crystallization, together with up-to-date input physics suitable for computing white dwarf evolution. The chemical profiles of Salaris et al (2000) consider carbon-oxygen white dwarfs in the mass range from 0.5 to 1.0 M ⊙ and take into account the presence of large abundances of oxygen in the central regions due to the high rates of the 12 C(α, γ) 16 O reaction.…”
Section: A2 Carbon-oxygen White Dwarfsmentioning
confidence: 99%
“…The high oxygen abundances in the central regions of the white dwarf minimize the effects of chemical differentiation upon crystallization as compared with the models in which a homogeneous 50/50 carbon and oxygen distributions throughout the star are adopted. For the sake of comparison, Salaris et al (1997) also considered a lower rate for 12 C(α, γ) 16 O reaction, which gives a smaller oxygen content at the center of the white dwarf. This leads to a larger heat capacity and therefore to a slower cooling rate.…”
Section: A2 Carbon-oxygen White Dwarfsmentioning
confidence: 99%
“…As the oxygen-rich solid core grows at the center of the white dwarf, the lighter carbon-rich liquid mantle left behind is efficiently redistributed by Rayleigh-Taylor instabilities (Isern et al 1997). This process releases gravitational energy, and this additional energy source has a substantial impact in the computed cooling times of cool white dwarfs (Segretain et al 1994;Salaris et al 1997;Montgomery et al 1999;Salaris et al 2000;Isern et al 2000;Renedo et al 2010).…”
Section: Introductionmentioning
confidence: 99%